Performance of Greater Yam Genotypes in Konkan Region under Rainfed Conditions - Mhaskar, N. V.; Jadye, A T; Bhagwat, N R; Haldankar, P M; Chavan, S A (JOURNAL OF ROOT CROPS, 2015)
Field experiments were conducted during 2006 to 2010 at Central Experiment Station, Wakawali, Maharashtra to evaluate the performance of six genotypes of greater yam viz., Sree Roopa, Da-11, Da.25, Da.168, Da.199 and Konkan Ghorkand for yield and quality. The trial was conducted in randomized block design with four replications. The pooled results showed that the genotype Da-199 produced the highest tuber yield of 29.29 t ha-1 and average tuber weight of 1.62 kg, which was significantly superior to all other genotypes. In multi-locational trials, it also produced significantly the maximum tuber yield of 21.39 t ha-1 over the rest of the genotypes in four different locations. Cultivation of Da.199 generated the maximum net return of ` 2,42,078 ha-1 and B:C ratio of 1.70. Among all the genotypes, Konkan Ghorkand and Da-199 had maximum score for all organoleptic characters.